2019
DOI: 10.1088/1755-1315/363/1/012016
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Indonesian Forest and Land Fire Controlling Operational Policies. Case Study: Siak Regency, Riau Province

Abstract: Indonesia has been struggling with forest and land fires for decades due to its large, multi-dimensional impacts. While less hotspots in 2016 were due to the La Nina, Indonesia has managed to reduce the hotspots in normal condition in 2017. However, there were indications that some of the policies were outside of the legal jurisdiction, e.g. to involve institutions out of their legal roles in fire controlling operations. Thus, this paper qualitatively discussed the analysis of fire controlling policy in Indone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
1
0
2
Order By: Relevance
“…Buruknya manajemen lahan gambut telah menyebabkan munculnya permasalahan yang sangat kompleks, yaitu meluasnya deforestasi, kebakaran hutan, meluasnya kawasan terdampak banjir tahunan, dan penurunan tanah (Saputra, 2019). Kebakaran hutan yang terjadi setiap tahun, terutama pada musim kemarau pada lahan gambut dengan kedalaman lebih dari 4 meter, menunjukkan itensitas yang selalu tinggi (Prayoto, 2011;Putra et al, 2019). Kebakaran hutan yang berulang menyebabkan hilangnya keanekaragaman hayati, berkurangnya penghasilan penduduk yang mata pencaharian tergantung dengan lahan gambut, dan memburuknya kesehatan masyarakat yang berkaitan dengan ISPA, seperti batuk dan pilek, flu, dan gangguan pernafasan (Nugraha, 2019;Saputra, 2019).…”
Section: Gambar 33 Peta Rasio Kerentanan Penduduk Indonesia Terhadap Covid-19unclassified
See 1 more Smart Citation
“…Buruknya manajemen lahan gambut telah menyebabkan munculnya permasalahan yang sangat kompleks, yaitu meluasnya deforestasi, kebakaran hutan, meluasnya kawasan terdampak banjir tahunan, dan penurunan tanah (Saputra, 2019). Kebakaran hutan yang terjadi setiap tahun, terutama pada musim kemarau pada lahan gambut dengan kedalaman lebih dari 4 meter, menunjukkan itensitas yang selalu tinggi (Prayoto, 2011;Putra et al, 2019). Kebakaran hutan yang berulang menyebabkan hilangnya keanekaragaman hayati, berkurangnya penghasilan penduduk yang mata pencaharian tergantung dengan lahan gambut, dan memburuknya kesehatan masyarakat yang berkaitan dengan ISPA, seperti batuk dan pilek, flu, dan gangguan pernafasan (Nugraha, 2019;Saputra, 2019).…”
Section: Gambar 33 Peta Rasio Kerentanan Penduduk Indonesia Terhadap Covid-19unclassified
“…Lemahnya tata kelola, termasuk pembagian kewenangan dan kemampuan pemerintah pada berbagai level, menyebabkan permasalahan lahan gambut di Kabupaten Siak belum bisa diselesaikan sepenuhnya secara optimal (Putra et al, 2019;Saputra, 2019).…”
Section: Gambar 33 Peta Rasio Kerentanan Penduduk Indonesia Terhadap Covid-19unclassified
“…Forest and land fires continue to occur despite the government's efforts to control them through rules and control programs. Numerous studies have shown that there are issues with managing forest and land fires, such as the inability of relevant agencies to coordinate, the lack of a division of authority and responsibility between relevant agencies, the institutional form being Ad Hoc, the lack of integration of policies for controlling forest and land fires, weak law enforcement, and a constrained budget (Purnomo et al, 2019;Putra et al, 2019;Zainal, 2016).…”
Section: Introductionmentioning
confidence: 99%